HIV DNA loads, plasma residual viraemia and risk of virological rebound in heavily treated, virologically suppressed HIV-infected patients. (January 2015) - Gianotti, N.; Canducci, F.; Galli, L.; Cossarini, F.; Salpietro, S.; Poli, A.; Nozza, S.; Spagnuolo, V.; Clementi, M.; Sampaolo, M.; Ceresola, E.R.; Racca, S.; et al.
Abstract: In this single-centre, retrospective study, we analyzed data of 194 patients receiving antiretroviral therapy with <50 human immunodeficiency virus (HIV) RNA copies/mL in plasma and 318 HIV RNA/DNA paired samples. By kinetic polymerase chain reaction (kPCR) molecular system analysis, 104 (54%) subjects had undetectable HIV RNA and 90 (46%) had residual viraemia. Median (interquartile range) HIV DNA load was 780 (380–1930) copies/10 6 peripheral blood lymphocytes (PBL), and HIV DNA loads were independently associated with residual viraemia (p 0.002). Virological rebound occurred in 29/194 (15%) patients over a median (interquartile range) follow-up of 17.5 (13.5–31.5) months. Residual viraemia (p 0.002), but not HIV DNA load, was independently associated with virological rebound.